An unusual cause of a haemothorax following pacemaker implantation: A case report. Issue 5 (1st May 2022) - Saunderson, Christopher E. D.; Hogarth, Andrew J.; Papaspyros, Sotiris; Tingerides, Costa; Tayebjee, Muzahir H.
Abstract: Background: Haemothoraces are a reported but extremely rare complication of pacemaker implantation. Haemothoraces can be a consequence of lead perforation through the right ventricle (RV) and pericardium into the pleural space, direct lung or vascular injury during access. Case summary: A 72-year-old woman presented 24 h after a pacemaker implantation with chest pain and shortness of breath. Computed tomography of the chest confirmed perforation of the RV lead into the left pleural cavity with a large left sided haemothorax. Following percutaneous drainage of the left sided haemothorax, the patient became haemodynamically unstable necessitating emergent sternotomy. During surgery, the extra-cardiac portion of the pacing lead was cut, the RV repaired and a large haematoma evacuated from the left pleural space. Despite this, the patient remained hypotensive, and further exploration showed a bleeding intercostal artery that had been lacerated by the pacing lead. This was treated by electrocautery, and the patient's haemodynamic status improved. The RV lead remnant was removed transvenously via the subclavian vein, and the patient was left with a single chamber atrial pacemaker. Discussion: Prompt recognition of RV lead perforation and its associated sequalae, often utilising multi-modality imaging, is vital to enable transfer to a centre with cardiac surgical expertise. In this case, the perforating RV lead lacerated an intercostal artery, and this was only identified at the time of surgery. In order to minimize the risk of perforation, multiple fluoroscopic views should be used, and care should be taken during helix deployment.